Conjuring Futures: Culture and Decolonization in the Dutch Caribbean, 1948–1975. Issue 2 (1st June 2019) - Schields, Chelsea
Abstract : This article explores the history of the Foundation for Cultural Cooperation between the Netherlands, Suriname, and the Netherlands Antilles (Sticusa), asking how cultural institutions partook in the process of decolonization. Analyzing the perspectives of Sticusa collaborators and critics in the Caribbean, I argue that cultural actors saw decolonization as an opportunity to reorient cultures toward an emergent world order. In this process, they envisioned a range of horizons, from closer integration with Europe to enhanced affinity with the broader Americas. By the 1970s, however, these horizons narrowed to the attainment of national sovereignty, and Sticusa's cultural experiment ended as a result.